2020
DOI: 10.1101/2020.03.23.003434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the molecular mechanisms contributing to the success of an invasive species across different ecosystems

Abstract: Invasive species provide an opportune system to investigate how populations respond to new environments. While the impacts of invasive species increase annually, gaps in our understanding of how these species adapt to introduced areas remain. Using the perennial forb Gypsophila paniculata, we investigated how invasive species respond to different environments.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Recent studies also found that any gene expression is based on Ecology. (Sarah et al 2020) [11] . Related to this trait any fecundity of any Fish may be Environmentally Controlled and Values are Negatively Correlated Both with the 'TDS' and 'CEC' and accordingly, fish may migrate depending on Total Dissolved Solids (TDS), Cation Exchange Capacity (CEC) has roles in migrations of species are also being studied (Das, 2020) [7,8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also found that any gene expression is based on Ecology. (Sarah et al 2020) [11] . Related to this trait any fecundity of any Fish may be Environmentally Controlled and Values are Negatively Correlated Both with the 'TDS' and 'CEC' and accordingly, fish may migrate depending on Total Dissolved Solids (TDS), Cation Exchange Capacity (CEC) has roles in migrations of species are also being studied (Das, 2020) [7,8,9] .…”
Section: Introductionmentioning
confidence: 99%